Seasonal changes in positive airway pressure adherence - Prigent, Arnaud; Blanloeil, Clément; Jaffuel, Dany; Serandour, Anne Laure; Barlet, Franck; Gagnadoux, Frédéric (Frontiers in Medicine, 2024)
Through their effects on sleep duragon, bedroom environments and pollen allergies, seasonal variagons may impact posigve airway pressure (PAP) adherence. We analyzed daily PAP tele monitoring data from 25 846 adults (median age 64 years, 67.8% male) treated with PAP for at least 4 months (mean (standard deviagon, SD) duragon of PAP: 5.5 years (SD 4.1)) to examine seasonal changes in PAP adherence, leaks and residual apnea-hypopnea index. We demonstrate a significant decrease in PAP adherence in June compared to January (mean (SD): 0.37 (1.54) hours/night) that achieved the minimal clinically important difference (MCID) of 30 minutes in 13.9% of adults. Furthermore, we provide novel data supporgng the associagon of rising temperatures with seasonal changes in PAP use. Indeed, the most pronounced decline in PAP adherence was observed during the hooest days while PAP adherence was only slightly reduced during the coolest days of June. Clinicians should be aware of seasonal changes in PAP adherence that are likely to be exacerbated by climate change.